Scenario-based life-cycle cost assessment to support sustainable investment in rural communal sanitation facilities: application to a school-based sanitation facility - N. M. Koseoglu (IWA Publishing, 2021)
Despite decades of investment in widening access to improved sanitation, much of the world still lacks access to functional sanitation facilities. Through much of the Global South, toilets are inoperable and often abandoned. Failure to understand and account for the whole-life cost of sanitation infrastructure, as well as the interplay between context-specific socio-economic determinants, is one explanation for this reduction in the service life of shared sanitation infrastructure. This issue is especially salient in school-based and communal facilities in middle- to low-income countries. Drawing on a case study of a sanitation facility in a government school in rural south India, we explore the relationship between user value, community-based capacity, and external support in determining the costs of operating and maintaining sanitation facilities over their lifetime. We develop a scenario-based life-cycle cost assessment methodology to examine the relational impact of these determinants on the ‘real’ cost of shared sanitation infrastructure. The analysis concludes that investment and interventions that stimulate demand and enhance the capacity of a community are the most cost-effective options for ensuring the sustainability of sanitation facilities in our case study site. We then reflect on the applicability and limitations of these findings for a wider range of communal sanitation facilities. HIGHLIGHTS Communal sanitation infrastructure's long-term functionality depends on its value to the community, the capacity of the community to contribute, and the availability of external support.; We develop a framework to explore the effects of these determinants on the life-cycle cost of communal sanitation infrastructure.; Results suggest that investment in capacity building and demand stimulation reduce the life-cycle cost.;